Foreign policies of states: a study of political variables and geographical constants - Abdul-Hussein, Hassan Nasser (The International and Political Journal, 2023)
This research focuses on the interaction of foreign and domestic policy, in particular how internal security, political stability, and sustainable development impact foreign policy. It gives particular attention to the importance of geographical constants in terms of location, space, borders, and neighbors in achieving the objectives of foreign policy and address challenges of national security. This paper investigates the importance of geography in security, economic, and strategic aspects, as well as discusses the issue of borders and its regional and international recognition in affecting relations with neighboring countries positively or negatively.